Determination of Anti-Browning Agents in The Manufacture of Flour from Kepok Banana Skin Waste - Nuraeni, Farida; Widiastuti, Diana; Herlina, Eka; Benedicta, Glisten Madeleine (Universitas Pakuan, 2024)
Kepok banana is one of the bananas which is a horticultural commodity, easy to cultivate and has high production value in Indonesia. The high production of bananas cannot be separated from the banana peel waste produced. The effort made is to process Kepok banana peels into flour. One of the problems that occurs is that bananas experience a browning reaction. This research aims to reduce the effects of browning reactions by determining anti-browning substances and optimum concentrations in the process of making kepok banana peel flour, so that it can be used as a food ingredient. Making kepok banana peel flour begins with preparing a sample of kepok banana peel and an anti-browning solution. The samples were immersed in each solution, namely Na2S2O5, C₆H₈O₆, and C₆H₈O₇ with a concentration of 0.1 – 0.2%. Control samples were prepared without soaking. Then it is dried, mashed and sifted until it becomes flour. Organoleptic tests and white degree tests were carried out on 6 samples and 1 control. Selected samples are then subjected to chemical tests in the form of proximate and minerals. The results of the organoleptic test and white degree test showed that sample T4, namely soaking using 0.2% Ascorbic Acid anti-browning solution, was the sample selected by the panelists and had the highest white degree, namely 53,26. The results of the proximate and mineral tests for T4 flour samples compared to T1 flour (control) showed that the T4 flour samples had proximate and mineral content values that largely met the standards for wheat flour according to SNI 3751:2009. Only the ash content exceeds the SNI standard, this can be caused by the high iron mineral content.